High-static cellulose acetate-based electret air filtering material and preparation method thereof
By performing high-voltage electrospinning in a mixed solution of cellulose acetate and CuSO4, composite nanofiber membranes were prepared, which solved the problem of weak electrostatic enhancement effect of cellulose acetate-based electret air filter materials, and significantly improved the filtration efficiency and service life.
Patent Information
- Application Number
- CN202411992667.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The electrostatic enhancement effect of cellulose acetate-based electret air filter material is relatively weak, resulting in insufficient filtration efficiency and service life.
By electrospinning the mixed solution of cellulose acetate and CuSO4 at high voltage, a composite nanofiber membrane was prepared to adjust the coordination between the hydroxyl groups and ester groups on Cu2+ and cellulose acetate, thereby enhancing the electrostatic construction effect of the material.
The filtration efficiency and service life of cellulose acetate-based electret air filter material is significantly improved, with the surface potential up to 12.52 kV, the filtration efficiency of PM 0.3 can reach 99.31%, and the filtration resistance is reduced.
Smart Images

Figure CN119633494A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of air filter material preparation, in particular to a high-static cellulose acetate-based electret air filter material and a preparation method thereof. Background Art
[0002] With the development of industrialization, air pollution has become a serious environmental problem. Pollutants in the air include toxic gases (i.e. ozone (O 3 ), sulfur dioxide (SO 2 ), nitrogen oxides (NOx) and volatile organic compounds (VOCs), suspended particulate matter (PM), viruses, etc., not only affect air quality, but also have a serious negative impact on ecosystems, climate change and human health. Therefore, it is urgent to develop air filter materials with high filtration efficiency and low resistance characteristics.
[0003] At present, electrostatically enhanced synthetic fiber materials have become the mainstream air filter materials (i.e., electret filter materials) due to their high charge storage stability, strong moisture resistance, and long service life. However, such materials are difficult to degrade and pose a threat to the ecological environment. Therefore, in order to protect the ecological environment, it is necessary to develop biodegradable air filter materials on this basis.
[0004] Cellulose acetate (CA) is an esterified derivative of cellulose. Due to its good biodegradability, biocompatibility and absorbability, cellulose acetate has become one of the most promising raw materials for preparing air filtration materials. However, there are a large number of hydrogen bonds between CA molecules, which makes the molecular chains tightly connected and difficult to move, which makes it difficult for the internal dipoles to be oriented and polarized under the action of the electric field, and the electrostatic enhancement effect of cellulose acetate-based electret air filter materials is relatively weak. In addition, the strong hydrophilicity imparted by the polyhydroxy structure on the fiber surface will accelerate the charge decay, which will greatly reduce the filtration efficiency and service life of the material. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a high-static cellulose acetate-based electret air filter material and a preparation method thereof, so as to solve the problem that the electrostatic enhancement effect of the cellulose acetate-based electret air filter material is relatively weak. The method is simple and has low preparation cost, and the filtration efficiency and service life of the cellulose acetate-based electret air filter material are greatly improved.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a high-static cellulose acetate-based electret air filter material comprises the following steps: S1, cellulose acetate and CuSO 4 The mixed solution of cellulose acetate and CuSO was electrospun at a voltage of 18-22 kV.4 The mass ratio of is 1:(0.01-0.04), and a composite nanofiber membrane is obtained; S2, removing excess solvent from the composite nanofiber membrane to obtain a high-static cellulose acetate-based electret air filter material.
[0007] A further improvement of the present invention is: The mixed solution described in S1 is obtained by the following process: S1 Cellulose acetate powder and CuSO 4 The powder was added to N,N-dimethylacetamide and acetone, and then stirred at 5-45°C for 6.5-7.5h until the cellulose acetate powder and CuSO 4 The powder is completely dissolved to obtain the mixed solution.
[0008] The mass ratio of the N,N-dimethylacetamide to acetone is 1:1.
[0009] The mass ratio of the total mass of the N,N-dimethylacetamide and acetone to the mass of the cellulose acetate powder is 83:17.
[0010] The electrospinning process described in S1 was carried out at 25-30 o C and an ambient relative humidity of 30% to 40%.
[0011] S1: Load the mixed solution into an injection syringe equipped with a metal needle, fix the nozzle of the injection syringe horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection syringe with the center of the negative electrode, keep the working room of the electrospinning instrument in a sealed state, and then perform electrospinning.
[0012] The distance from the metal needle of the injection needle tube to the center of the negative electrode is 16-18 cm.
[0013] The flow rate during S1 electrospinning was 0.015~0.018 ml / min.
[0014] S2 removes excess solvent in the composite nanofiber membrane by vacuum drying, and the vacuum drying is performed at 60° C. for 3 h.
[0015] A high-static cellulose acetate-based electret air filter material obtained by any one of the above-mentioned methods for preparing a high-static cellulose acetate-based electret air filter material.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a high-static cellulose acetate-based electret air filter material, wherein the method comprises adjusting cellulose acetate and CuSO 4The ratio of Cu 2+ The interaction between the hydroxyl and ester groups on CA changes the crystal structure of the CA molecule to enhance its activity and independent polarization characteristics, and then electrospinning is performed through appropriate voltage to improve the electrostatic construction effect; since the multi-hydroxyl structure on the fiber surface is eliminated, the charge decay will be greatly alleviated, and the filtration efficiency and service life of the material will be greatly improved. 2+ The coordination with the oxygen-containing functional groups on CA changes the crystal structure of CA, thereby enhancing its activity and independent polarization properties, producing a prominent dipole moment (8.86 debye) and electrostatic building effect, with a surface potential of up to 12.52 kV, and a PM 0.3 filtration efficiency of 99.31%, which is 39.98% higher than the filtration efficiency of CA membrane. The molecular chain spacing of CA is expanded to prepare a high-static cellulose-based air filter material. The present invention overcomes the problems of the non-degradability and environmental pollution of existing electret filter materials, and prepares a high-static cellulose acetate electret air filter material (CA-Cu) with the assistance of copper ions. 2+ Compared with CA membrane, electret filter membrane has obvious electrostatic enhancement effect and significantly improved filtration performance, and is expected to be used in actual production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 CA-Cu 2+ Schematic diagram of the preparation process of composite electret air filter material.
[0018] Figure 2 This is a SEM image of the CA film described in Comparative Example 1 of the present invention at a magnification of 5K.
[0019] Figure 3 This is a SEM image of the CA film described in Comparative Example 1 of the present invention at a magnification of 10K.
[0020] Figure 4 This is a diameter analysis diagram of the CA membrane described in Comparative Example 1 of the present invention.
[0021] Figure 5 CA-Cu as described in Example 4 of the present invention 2+ SEM image of the composite film at 5K magnification.
[0022] Figure 6 CA-Cu as described in Example 4 of the present invention 2+ SEM image of the composite film at 10K magnification.
[0023] Figure 7 CA-Cu as described in Example 4 of the present invention 2+ Diameter analysis diagram of composite membranes.
[0024] Figure 8 CA-Cu as described in Example 4 of the present invention 2+ EDS C element distribution spectrum of the composite film.
[0025] Fig. 9 CA-Cu as described in Example 4 of the present invention 2+ O element distribution spectrum of composite film EDS.
[0026] Fig.10 CA-Cu as described in Example 4 of the present invention 2+ EDS distribution spectrum of Cu element of composite film.
[0027] Fig.11 CA-Cu as described in Example 4 of the present invention 2+ Surface potential map of the composite films.
[0028] Fig.12 CA-Cu as described in Example 4 of the present invention 2+ Filtration performance and quality factor diagram of composite membrane for PM 0.3. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0030] The present invention discloses a high-static cellulose acetate-based electret air filter material (i.e., cellulose acetate / Cu 2+ The preparation method of composite electret air filter material is as follows: Figure 1 As shown, the specific steps are as follows: Step 1: weigh 1.7 g of cellulose acetate powder (CA) and 0.017-0.068 g of CuSO 4 The powder was dissolved in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio was 1:1).
[0031] Step 2, stirring the solution in (1) at 5-45° C. for 6.5-7.5 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0032] Step 3: Load the obtained spinning solution into an injection syringe equipped with a metal needle, then fix the nozzle of the injection syringe horizontally on the injection device (injection pump), connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection syringe with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0033] Step 4: Set the working room temperature to 25-30°C during electrospinning. oC, the relative humidity of the environment is 30%~40%, the voltage of the high-voltage power supply is 18~22 kV, the distance from the needle to the center of the roller is 16~18 cm, and the spinning flow rate is 0.015~0.018ml / min.
[0034] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0035] Embodiment 1: Step 1: weigh 1.7 g of cellulose acetate powder (CA), 0.017 g of CuSO 4 The powder was dissolved in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio was 1:1).
[0036] Step 2, stirring the solution in (1) at 25° C. for 7 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0037] Step 3: Load the obtained spinning solution into an injection needle tube equipped with a metal needle, then fix the injection needle tube horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection needle tube with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0038] Step 4: Set the working chamber temperature to 27 o C, the relative humidity of the environment was 35%, the voltage of the high-voltage power supply was 20 kV, the distance from the needle to the center of the drum was 18 cm, and the spinning flow rate was 0.017 ml / min.
[0039] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0040] The beneficial effects of the present invention are: using CA-Cu 2+ The surface potential of the prepared electret filter membrane can reach 5.50 kV, the filtration efficiency of PM 0.3 can reach 96.16%, the filtration resistance is only 27.9 Pa, and the quality factor ( ) reaches 0.118pa -1 .
[0041] Embodiment 2: Step 1: weigh 1.7 g of cellulose acetate powder (CA), 0.034 g of CuSO 4 The powder was dissolved in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio was 1:1).
[0042] Step 2, stirring the solution in (1) at 25° C. for 7 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0043] Step 3: Load the obtained spinning solution into an injection needle tube equipped with a metal needle, then fix the injection needle tube horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection needle tube with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0044] Step 4: Set the working chamber temperature to 27 o C, the relative humidity of the environment was 35%, the voltage of the high-voltage power supply was 20 kV, the distance from the needle to the center of the drum was 18 cm, and the spinning flow rate was 0.017 ml / min.
[0045] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0046] The beneficial effects of the present invention are: using CA-Cu 2+ The surface potential of the prepared electret filter membrane can reach 6.09 kV, the filtration efficiency of PM 0.3 reaches 96.43%, the filtration resistance is only 28.5 Pa, and the quality factor reaches 0.118 Pa -1 .
[0047] Embodiment 3: Step 1: weigh 1.7 g of cellulose acetate powder (CA), 0.051 g of CuSO 4 The powder was dissolved in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio was 1:1).
[0048] Step 2, stirring the solution in (1) at 25° C. for 7 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0049] Step 3: Load the obtained spinning solution into an injection needle tube equipped with a metal needle, then fix the injection needle tube horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection needle tube with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0050] Step 4: Set the working chamber temperature to 27 o C, the relative humidity of the environment was 35%, the voltage of the high-voltage power supply was 20 kV, the distance from the needle to the center of the drum was 18 cm, and the spinning flow rate was 0.017 ml / min.
[0051] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0052] The beneficial effects of the present invention are: using CA-Cu 2+ The surface potential of the prepared electret filter membrane can reach 6.27 kV, the filtration efficiency of PM 0.3 reaches 99.31%, the filtration resistance is only 40 Pa, and the quality factor reaches 0.128 Pa -1 .
[0053] Embodiment 4: Step 1: weigh 1.7 g of cellulose acetate powder (CA), 0.051 g of CuSO 4 The powder was dissolved in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio was 1:1).
[0054] Step 2, stirring the solution in (1) at 35° C. for 7 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0055] Step 3: Load the obtained spinning solution into an injection needle tube equipped with a metal needle, then fix the injection needle tube horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection needle tube with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0056] Step 4: Set the working chamber temperature to 27 o C, the relative humidity of the environment was 35%, the voltage of the high-voltage power supply was 20 kV, the distance from the needle to the center of the drum was 18 cm, and the spinning flow rate was 0.017 ml / min.
[0057] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0058] The beneficial effects of the present invention are: using CA-Cu 2+ The surface potential of the prepared electret filter membrane can reach 7.97kV, the filtration efficiency of PM 0.3 reaches 99.15%, the filtration resistance is only 37.3Pa, and the quality factor reaches 0.131pa -1 .
[0059] Embodiment 5: Step 1: weigh 1.7 g of cellulose acetate powder (CA), 0.068 g of CuSO 4 The powder was dissolved in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio was 1:1).
[0060] Step 2, stirring the solution in (1) at 45° C. for 7 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0061] Step 3: Load the obtained spinning solution into an injection needle tube equipped with a metal needle, then fix the injection needle tube horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection needle tube with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0062] Step 4: Set the working chamber temperature to 28 o C, the relative humidity of the environment was 35%, the voltage of the high-voltage power supply was 20 kV, the distance from the needle to the center of the drum was 18 cm, and the spinning flow rate was 0.017 ml / min.
[0063] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0064] The beneficial effects of the present invention are: using CA-Cu 2+ The surface potential of the prepared electret filter membrane can reach 12.52 kV, the filtration efficiency of PM 0.3 reaches 93.79%, the filtration resistance is only 30.5 Pa, and the quality factor reaches 0.092 Pa -1 .
[0065] Comparative Example 1: Step 1: weigh 1.7 g of cellulose acetate powder (CA) and dissolve it in 8.3 g of a mixed solvent of N,N-dimethylacetamide (DMAc) and acetone (Ac) (the solvent mass ratio is 1:1).
[0066] Step 2, stirring the solution in (1) at 25° C. for 7 hours to completely dissolve it, thereby obtaining a spinning solution with a certain viscosity.
[0067] Step 3: Load the obtained spinning solution into an injection needle tube equipped with a metal needle, then fix the injection needle tube horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection needle tube with the center of the roller, and keep the working room of the electrospinning instrument in a sealed state.
[0068] Step 4: Set the working chamber temperature to 27 o C, the relative humidity of the environment was 35%, the voltage of the high-voltage power supply was 20 kV, the distance from the needle to the center of the drum was 18 cm, and the spinning flow rate was 0.017 ml / min.
[0069] Step 5, placing the composite nanofiber membrane obtained by electrospinning in a vacuum oven at 60° for 3 h to remove excess solvent.
[0070] The beneficial effects of the present invention are: using CA-Cu 2+ The surface potential of the prepared electret filter membrane can reach 1.17 kV, the filtration efficiency of PM 0.3 reaches 70.83%, the filtration resistance is 36 Pa, and the quality factor reaches 0.0342 Pa. -1 .
[0071] Figure 2 , Figure 3 and Figure 5 , Figure 6 Comparative analysis of CA film and CA-Cu by SEM images 2+ The fiber diameter of the composite membrane changes. Figure 4 and Figure 7 Comparative analysis of CA membrane and CA-Cu by bar graph 2+ From the change of fiber diameter of the composite membrane, it can be found that due to the addition of copper sulfate, the conductivity of the spinning solution increases and the fiber diameter decreases.
[0072] Figure 8 The distribution of C element in the composite film is shown. Fig. 9 The distribution of O element in the composite film is shown. Fig.10 The distribution of Cu element in the composite film is shown. The Cu element is evenly distributed without agglomeration.
[0073] from Fig.11 It can be seen that the surface potential increases with the CuSO 4 The content increases and becomes larger, CuSO 4 The content is 0.068g, and the surface potential is maximum when the reaction temperature is 45℃.
[0074] from Fig.12 It can be seen that when CuSO 4 When the content is 0.051g and the reaction temperature is 35℃, the filtration performance of the composite membrane is the best, with filtration efficiency: 99.15%, filtration resistance: 37.3 Pa, and quality factor: 0.131Pa -1 , indicating that Cu 2+ The coordination indeed enhances the electrostatic adsorption of the composite membrane.
Claims
1. A method for preparing a high-static cellulose acetate-based electret air filter material, characterized in that: The steps include: S1, electrospinning a mixed solution of cellulose acetate and CuSO4 at a voltage of 18-22 kV, wherein the mass ratio of cellulose acetate to CuSO4 is 1:(0.01-0.04), to obtain a composite nanofiber membrane; S2, removing excess solvent from the composite nanofiber membrane to obtain a high-static cellulose acetate-based electret air filter material.
2. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 1, characterized in that: The mixed solution described in S1 is obtained by the following process: S1: adding cellulose acetate powder and CuSO4 powder to N,N-dimethylacetamide and acetone, and then stirring at 5-45° C. until the cellulose acetate powder and CuSO4 powder are completely dissolved to obtain the mixed solution.
3. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 2, characterized in that: The mass ratio of the N,N-dimethylacetamide to acetone is 1:
1.
4. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 3, characterized in that: The mass ratio of the total mass of the N,N-dimethylacetamide and acetone to the mass of the cellulose acetate powder is 83:
17.
5. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 1, characterized in that: The electrospinning process described in S1 was carried out at 25-30 o C and an ambient relative humidity of 30% to 40%.
6. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 1, characterized in that: S1: Load the mixed solution into an injection syringe equipped with a metal needle, fix the nozzle of the injection syringe horizontally on the injection device, connect the positive electrode of the high-voltage power supply of the electrospinning instrument to the metal needle, wrap the non-woven fabric on the roller-shaped negative electrode, align the injection syringe with the center of the negative electrode, keep the working room of the electrospinning instrument in a sealed state, and then perform electrospinning.
7. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 6, characterized in that: The distance from the metal needle of the injection needle tube to the center of the negative electrode is 16-18 cm.
8. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 1, characterized in that: The flow rate during S1 electrospinning was 0.015~0.018 ml / min.
9. The method for preparing a high-static cellulose acetate-based electret air filter material according to claim 1, characterized in that: S2 removes excess solvent in the composite nanofiber membrane by vacuum drying, and the vacuum drying is performed at 60° C. for 3 h.
10. A high-static cellulose acetate-based electret air filter material obtained by the preparation method of the high-static cellulose acetate-based electret air filter material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of nanometer fibers for purifying organic pollutants in air
CN103668513A
Method for producing gas filtering material by needle-free electrostatic spinning technology and application of gas filtering material
CN105780298A
Nano-copper regenerated cellulose fiber and preparation method thereof
CN105951200A
Modified cellulose ultrafiltration membrane and preparation method thereof
CN114832648A
Cellulose acetate nanofiber membrane as well as preparation method and application thereof
CN115652527A